Nephrotoxicity of platinum derivatives in children – a review of the literature - Stefanowicz, Joanna; Owczuk, Radosław; Iżycka-Świeszewska, Ewa; Rückemann-Dziurdzińska, Katarzyna; Balcerska, Anna (Contemporary Oncology/Współczesna Onkologia, 2011)
This manuscript presents a review of the literature about nephrotoxicity of platinum derivatives, which are commonly used in paediatric oncology, such as cisplatin and carboplatin. It shows the incidence, pathomechanisms, risk factors, type and clinical features of the disorders. It presents differences in nephrotoxic effects of particular drugs, and describes possibilities of early detection and monitoring of clinical course and therapy. It emphasises the role of nephroprotective treatment. Hypomagnesaemia and decreased glomerular filtration rate (GFR) are the most common clinical manifestations of cisplatin and carboplatin nephrotoxicity. The assessment of kidney function during active antineoplastic treatment and after termination of the therapy is one of the key diagnostic elements permitting the prompt diagnosis of the side-effects of the therapy. The awareness of the risk factors predisposing to drug-induced nephrotoxicity influences its incidence and permits the application of suitable procedures aimed at kidney protection.